Diversity and abundance of insects in the recreational forest of Bukit Keluang, Besut, Terengganu - Noor Ain Abdullah (2022)
Bukit Keluang is one of the famous natural recreational sites in Besut, Terengganu due to their beautiful sandy beaches and beautiful landscapes. Bukit Keluang recreational forest consist coastal and lowland dipterocarp forest. The studies on the biodiversity are never been reported at this area and thus, we aimed to investigate the diversity and abundance of insects in the coastal and inland forest of Bukit Keluang recreational forest. We built two plots which are Plot A in the coastal area and Plot B in the inland forest at Bukit Keluang. For each plot, three types of insect traps were used; yellow pan traps, pitfall traps, and Malaise traps. The traps were left for seven days and all insect samples collected were brought to the laboratory for sorting, enumerating and identifying up to order level. A total of 455 individuals of insects consisted of 10 orders (i.e. Hymenoptera, Diptera, Lepidoptera, Coleoptera, Collembola, Homoptera, Orthoptera, Dermaptera, Blattodea and Isoptera) were successfully collected from the forest of Bukit Keluang. Among them, Hymenoptera order dominated the number of individuals collected at 67.25% followed by Diptera (11.21%) whilst Collembola and Dermaptera were the least abundance order collected at 0.22%, respectively. The coastal forest recorded a total of 271 individuals (nine orders) while inland forest recorded 184 individuals (eight orders). No significant difference (p>0.05) of insect abundance was recorded between both plots.However, the Shannon-Weiner Diversity Index (H’) showed that the diversity of insects in the inland forest was slightly higher (H’=1.52)than the coastal forest (H’=0.86). We conclude that the insects’ diversity in Bukit Keluang is relatively higherin inland forest but lower in coastal forest. As no other insect survey has been conducted in this study area in the past, this study delivers a basic evidence and dataset of diversity and abundance for insect which may beneficial for further conservation research at Bukit Keluang in the future.